Recurrent status epilepticus: Clinical features and recurrence risk in an adult population. (April 2022) - Orlandi, Niccolò; Gozzi, Andrea; Giovannini, Giada; Turchi, Giulia; Cioclu, Maria Cristina; Vaudano, Anna Elisabetta; Meletti, Stefano
Highlights: A significative proportion of patients surviving a first incident SE experienced SE recurrence. The highest recurrence' s risk was observed within 6 months from the index event. SE remote and progressive etiologies gies and treatment super-refractoriness were associated with SE recurrence. SE recurrence did not influence longterm outcome. Abstract: Background: Knowledge regarding consequences among status epilepticus (SE) survivors is still scarce. We assessed the risk of recurrence in a cohort of first-ever adult SE survivors, comparing the clinical features of patients with recurrent and incident events. Methods: We reviewed our prospective register of consecutive SE patients, from September 1st 2013 to September 1st 2020. We excluded post-anoxic events and those patients with a SE prior the study period. We examined the effect of clinical predictors on the risk of subsequent SE through Cox proportional hazard regression, while the risk of recurrence was estimated through a survival analysis. Results: 430 patients were considered (mean follow-up: 23.3 months). 44 patients experienced SE recurrence, whereas 386 patients presented an isolated event. The highest risk of recurrence was observed within 6 months from the index event (7.9%), whereas the cumulative recurrence rate was 9.5%, 13%, and 20.5% at 6 months, 1 year, and 4-years respectively. SE recurrence was independently associated to remote (HR 2.8 - 95% CI 1.4 to 6.0) or progressive symptomatic etiologies (HR 3.9 - 95% CI 1.8 to 8.7) and it was higher for Super-Refractory SE (SRSE) cases (HR 3.3 - 95% CI 1.4 to 7.8). High STESS values ( p  = 0.01) and SE refractoriness ( p  = 0.01) were associated with early relapses (within 6 months from the index event). Conclusions: SE recurrence involved a significantly proportion of our cohort. Etiology other than acute symptomatic and SRSE were independently associated with a higher risk of recurrence, in particular within 6 months from the index event.